Strategi Mahasiswa dalam Memecahkan Permasalahan Non Rutin pada Materi Aljabar - Hidayat, Taufiq, Masduki, M.Si (2017)
This objective of the research is describing the strategy of the student in solving a non-routine problems using the arning method based on the solving problem on algebraic. The qualitative method is used for the research. In addition, the research has been conducted at Universitas Muhammadiyah Surakarta on first semester in academic year of 2016/2017. The first year students at Class A are selected as the ubject of the study. The observation method, evaluation test and interview are used for data collection. The data is analyzed using three ways method. Several valuable findings are found in this study such as (1) the high talented student use the strategy of Solving a Simpler Analogous Problem and Adopting a Different Point of View. The Solving a Simpler Analogous Problem strategy is used for solving a non-routine problem of both high order and simple order roots with multiply both top and bottom by the conjugate. In the regard of the logarithmic equation, it is solved by applying the logarithmic properties. Meanwhile, the strategy of Different Point of View is used for solving a non-routine question of high order roots by applying the properties of the exponential; (2) the fair talented student only use the strategy of Simplifying Problem by multiply both top and bottom by the conjugate for both high and simple order problems and applying the logarithmic properties for logarithmic problem; (3) the less talented student use the combination of the Simplifying Problem and the Intelligent Guessing and Testing. However, the reason for using the Intelligent Guessing and Testing method is due to the limitation of the student in the next steps and the limited understanding of the corresponding concept.